PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DILENGKAPI MEDIA KARTU SOAL TERHADAP MINAT BELAJAR SISWA PADA MATERI IKATAN KIMIA DI SMK MUHAMADIYAH CERENTI - Asnita Asnita (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
Problem Based Learning model of learning opportunities for students to be active in the learning process.The study aims to determine the effect of Problem Based Learning model equipped with question cards on students’ learning interest in chemical bonding material at Muhammdiyah Cerenti. The method used was quasi-exsperiment by applying a treatment condition to the control group and comparing the control group, using a sample of 65 people. Data collection techniques in this study are scale if interest and documentation. The final data processing result obtained sig (2-tailed) value p value 0,046< α (0,05 ) then H0 is rejected, this means that there is influence of Problem Based Learning model equipped with a question card for students’ learning interest in chemical bonding material at Muhammadiyah Cerenti. Kata Kunci : Problem Based Learning; kartu soal; minat belajar siswa